Restoration of uterine redox-balance by methanolic extract of Camellia sinensis in arsenicated rats - Dey, Arindam; Chattopadhyay, Sandip; Jana, Suryashis; Giri, Mukul Kumar; Khatun, Shamima; Dash, Moumita; Perveen, Hasina; Maity, Moulima (Acta Biologica Szegediensis, 2018)
Arsenic, an environmental and industrial pollutant causes female reproductive disturbances and female infertility. Several researchers found that the use of Camellia sinensis (CS) (green tea) is effective as an alternative therapeutic strategy in the management of several health ailments. This study explores the role of CS extract against arsenic-induced rat uterine tissue damage. Methanolic extract of CS (10 mg/kg BW) was tested concomitantly in arsenic-treated (10 mg/kg BW) rats for a duration of two-oestrous cycle length (8 days). CS effectively attenuated arsenic-induced antioxidantdepletion and necrosis in uterine tissue. Rats treated with sodium arsenite showed significantly reduced activities of enzymatic antioxidants like superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) in uterine tissue as evidenced by the results of spectrophotometric and electrozymographic analysis. Co-administration of CS significantly reversed the above oxidative stress markers in uterine tissue along with the histopathological changes in ovarian and uterine tissue. Moreover, an increase in the level of transcription factor NF-κB in the uterine tissue in association with reduced serum levels of vitamin B12 and folic acid were mitigated in arsenic fed rats following CS co-administration.